Fabrication of [60] Fullerene Grafted Polymer: Self-Assembly Behavior in Polar Solvents - Haldorai*, Yuvaraj; Naoshad Islam, Muhammad; Shim, Jae-Jin (Asian Journal of Chemistry, 2014)
In this report, we prepared a new type of [60] fullerene grafted poly(2-bromomethyl)acrylic acid. First step was the free-radical polymerization of 2-(bromomethyl)acrylic acid by using 2,2'-azobisisobutyronitrile. Then a nucleophilic substitution reaction was performed to substitute the bromine atoms present in the polymer with azide groups. Finally, the C60 grafted polymer was prepared by the reaction of azido functionalized polymer with C60. Results of Fourier transform infrared spectroscopy and ultraviolet-visible spectroscopy indicated that the C60 was chemically bonded to the polymer. The aggregation behavior of the resulting polymer in polar solvents was studied by transmission electron microscopy. The resultant polymer retained both electronic property of the C60 moiety and processability property of the polymer.